Serum uric acid to HDL-cholesterol ratio could be promising predictor of atrioventricular nodal reentrant tachycardia (Annals of Medical Research, 2023)
Aim: Paroxysmal supraventricular tachycardia (PSVT), particularly atrioventricular nodal reentrant tachycardia (AVNRT), is a common arrhythmia with no associated structural heart disease. Inflammation has been implicated in the pathogenesis of arrhythmias. Uric acid to high density lipoprotein (HDL)-cholesterol ratio (UHR) is a novel inflammation marker that has been investigated in various conditions. This study aimed to explore the potential association between UHR and AVNRT.Materials and Methods: A total of 136 patients were included in the study, including 86 patients with AVNRT and 50 controls with normal electrophysiological study. All patients' medical records were reviewed, and data were obtained retrospectively. We recorded baseline features, hematologic and biochemical markers, and determined the UHR value.Results: UHR (p=0.031) and uric acid (p 14.05 for predicting AVNRT with 56% sensitivity and 76% specificity.Conclusion: This study identifies UHR as a promising predictor for AVNRT, shedding light on the potential role of inflammation in the arrhythmia's development. Utilizing UHR as a readily accessible marker in the evaluation of AVNRT patients may have clinical implications.
Keywords: Arrhythmia; Supraventricular tachycardia; AVNRT; Uric acid/HDL ratio